Effects of Lavender Oil Aromatherapy on Pain, Anxiety, and Comfort after Cesarean Section: A Randomized Controlled Trial - Sevban Arslan; Evşen Nazik; İpek Köse Tosunöz; Sevgi Deniz Doğan; Seda Karaçay Yıkar (Journal of Nursology)
Objective: This study aims to determine the effects of lavender oil aromatherapy on pain, anxiety, and comfort after cesarean section.Methods: This study was conducted as a three-group randomized and controlled trial conducted in a city hospital in Adana, Türkiye between August and December 2020.The study included 93 women who had cesarean section, with 30 women in the experimental group, 31 women in the placebo group, and 32 women in the control group. The study was conducted in four phases including before the cesarean and 1st, 4th, and 8th hours post-cesarean section. Data were collected through the “Personal Information Form”, the “Visual Analogue Scale (VAS)”, the “Trait Anxiety Inventory (TAI)”, the “State Anxiety Inventory (SAI)”, and the “Postpartum Comfort Scale (PCS)”. Results: The women in the experimental, control and placebo groups were found to demonstrate statistically significant differences in terms of their VAS mean scores according to the processes (P<.001). The women in the experimental and control group demonstrated statistically significant differences in terms of their SAI mean scores (P<.05). Statistically significant differences were found between the experimental group women's physical comfort, socio-cultural comfort, and PCS total mean scores according to the processes (P<.05). Conclusion: The results of this study suggest that lavender oil aromatherapy can be used to decrease pain and anxiety and increase comfort after a cesarean section.